As condições de trabalho no SUAS no contexto de flexibilização das relações trabalhistas no estado do Espírito Santo - Rocha, Lutz Franthesco da Silva (2021)
The present study is anchored in the understanding that the advance of neoliberalism, the productive restructuring and the capital crisis deepen the precariousness of work in the Social Assistance Policy. As a general objective of the present study, it was sought to analyze the working conditions and relationships of higher education technicians from the CRAS and CREAS Units in the state of Espírito Santo, in the context of flexibilization of labor relations, between 2013 and 2017, aiming to reveal the capital crisis and the logic of permanent fiscal adjustment have an impact on this social policy and have an impact on working conditions and relations. For specific objectives a) To understand work in bourgeois sociability and the impacts of the capital crisis on female workers; b) Analyze the impact of the State's counter-reform on Social Policies and SUAS and, particularly, on Public Service workers; c) To characterize the socio-professional profile of the Higher Education Technicians of CRAS and CREAS in the state of Espírito Santo; d) Identify the forms of commercialization of the workforce in SUAS in order to highlight the types of bonds and their working conditions. The methodology included bibliographic research, documentary research and analysis of statistical data. In seeking to understand work in bourgeois sociability and the impacts of the capital crisis on female workers, it brought to light fundamental elements of the capitalist mode of production and its contradictions. Briefly, we also sought to analyze the impact of the State's counter-reform on Social Policies and more closely on SUAS. With such emphasis, it was possible to understand how the attacks on existing policies distort their social protection bias and how they undermine the meager achievements of the working class. The data point to precarious links with most of them composed of outsourced workers, the turnover given the precarious link and the variation and inconsistency in the data on care, which leads us to question the quality of the offer in this social policy.